Penerapan Manajemen Risiko pada Usaha Mikro: Studi Kasus UMKM Galon Isi Ulang “Biru” - Mohammad Ramadhika Gautama Kartiwa; Afrian Insan Kamil; Anggi Mahmuddin; Muhamad Zaki; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to assess the condition of the “Biru” refill-gallon business through SWOT analysis and risk identification. The research uses a qualitative descriptive method based on observations and employee interviews. The findings show that “Biru” has several strengths, including affordable prices, a strategic location in a densely populated area, RO and UV filtration technology, and convenient delivery services. However, the business also faces weaknesses, mainly its dependence on PDAM water and electricity, as well as manual financial recording. The risk analysis indicates that the highest threats come from operational and financial factors, such as water supply disruptions, power outages, and high maintenance costs. Mitigation efforts include regular machine maintenance, preparing reserve funds, and maintaining production-area cleanliness. Overall, “Biru” still has significant growth potential by maintaining water quality, improving service, and strengthening its business management.